ASSESSMENT OF FACTORS INFLUENCING YOUTH PARTICIPATION IN AGRICULTURAL-BUSINESS IN WESTERN AGRICULTURAL ZONE OF BAUCHI STATE, NIGERIA - Maigari, N. I.; Abu, I. A.; Sulaiman, A. (Nigerian Journal of Agriculture and Agricultural Technology, 2023)
The study examines the factors influencing youth participation in agricultural business in the western agricultural zone of Bauchi state. The data were collected using structured questionnaire and were analyzed using descriptive and inferential statistics. Multi stage random sampling technique was used in selecting 384 respondents. The results revealed that 36.4% and 34.5% of the respondents were within the age bracket of 25-29 and almost all (97.3%) of the respondents were males and most (63.6%) were married. The result also showed that more than half (59.1%) of the respondents had primary education while 24.5%, and 16.4% of the respondents had secondary, and higher education, respectively. The results further reveal that 41.8% of the respondents had 1-2 persons as their households. The occupational distribution of respondents showed that most (86.4%) of the respondents were business people (traders) and 13.6% were civil servants and had been in agribusiness for 1-5 years (10.0%), 39.1% for 5-9 years with majority (61.6%) not having agribusiness background while only 38.4% indicated to have agribusiness background. Different types of agribusiness youths participated in the study area were identified in which almost all (97.6%), (94.3%) and (86,5%) of the youths participated in livestock business, agro-marketing and crop production, respectively with majority (62.4%). The results further depicted educational level, access to extension and access to credit were found to be positively significant at 5% levels of significance. The constraints to youths’ participation in agribusiness were poor infrastructure such as roads, electricity, derailed support for local industries and negative impacts of climate change were ranked 1st, 2nd and 3rd. it was concluded that youth’s participation in agribusiness in the study area is low with more participation in crop and livestock production,level of education, access to extension service and credit facilities were significantly influencing youth participation in agribusiness (P = 0.045, P = 0,043 and P = 0.037 respectively). A lot of challenges constrained youth’s participation in agribusiness but they are mostly institutional. The study recommended that; extension and advisory services be improved to enable access to timely and relevant agricultural information, capacity building programmes should be organized to boost the skills of the youth in agricultural businesses, robust agricultural policies should be formulated and implemented. There should be efforts to improve youth attitudes by promoting the willingness and ability to engage in agribusiness, innovative ideas, and positive perceptions and access to credit facilities should be increased through loans from commercial banks cooperative savings.